Chemoradiation: A new approach for the treatment of cervical cancer. Issue 5 (1st August 2003) - Loizzi, V.; Cormio, G.; Loverro, G.; Selvaggi, L.; Disaia, P. J.; Cappuccini, F.
Abstract : Despite advances in screening, cervical cancer remains a major health problem worldwide. In an effort to improve loco-regional control, both neoadjuvant and chemoradiation have been trialed. Recently, five randomized clinical trials performed by the Gynecologic Oncology Group, the Radiation Therapy Oncology Group and the Southwest Oncology Group have demonstrated a significant advantage both in progression-free and overall survival when cisplatin-based chemotherapy was administered during radiation for advanced stages of cervical cancer. Based on the results of these trials, the US National Cancer Institute released a Clinical Announcement supporting the concurrent use of cisplatin-based chemotherapy with radiation therapy for high-risk early stage and locally advanced stage cervical cancer. Subsequently, an additional prospective randomized trial performed by the National Cancer Institute of Canada was not able to show benefit with the use of chemoradiation compared with radiation alone for patients with locally advanced stage cervical cancer. This article will analyze these six clinical trials in order to determine the role of chemoradiation in the management of patients with cervical cancer. Furthermore, as anemia is one of the most powerful prognostic factors in patients with cervical cancer, we propose to evaluate the relationship between a decreased level of hemoglobin and treatment outcome.